Pengaruh Perbedaan Media Dan Periode Transportasi Terhadap Pertumbuhan Bibit Rumput Laut (Kappaphycus alvarezii) - Ali, Mahrus; Putri, Berta; Romadoni, Soma (AQUASAINS, 2015)
Brown seaweed (Kappaphycus alvarezii) is one of the important aquaculture commodities in Indonesia. Tissue culture seaweed seed has higher quality than the natural ones, but tissue culture seaweed seed still imported from a specific area. Media and transportation period effect the seed freshness. The study was conducted to determine the effective of transportation medium and the optimal of transportation period. The study was conducted in the Ketapang’s marine, South Lampung. The study using experimental methods with completely randomized factorial design with two treatments and three replication for each treatment. The first treatment is the difference transport media (banana stem and sponge), and the second treatment is the difference transport period (24, 48, and 72 hours). The parameters observed were transport temperature, the seed freshness, seaweed growth weight, and water quality factor (pH, dissolved oxygen, salinity, temperature, water clarity, and flow velocity). The results showed that the seaweed was transported by the media banana stem had seed freshness and weight growth higher quality than the sponge media, and the transportation period affected the seed freshness and the seaweed growth weight.